The politics of Estonia's offshore wind energy programme: Discourse, power and marine spatial planning. (February 2019) - Tafon, Ralph; Howarth, David; Griggs, Steven
There is growing recognition that marine spatial planning is an inherently political process marked by a clash of discourses, power and conflicts of interest. Yet, there are very few attempts to make sense of and explain the political practices of marine spatial planning protests in different contexts, especially the way that planners and developers create the conditions for the articulation of objections, and then develop new strategies to negotiate and mediate community resistance. Using poststructuralist discourse theory, the article analyses the politics of a proposed offshore wind energy project in Estonia within the context of the country's marine spatial planning processes. First, through the lens of politicization, it explores the strategies of political mobilization and the rival discourses of expertise and sustainability through which residents and municipal actors have contested the offshore wind energy project. Secondly, through the lens of depoliticization, it explains the discursive and legalistic strategies employed by developers, planners and an Administrative Court to displace – spatially and temporally – the core issues of contestation, thus legitimizing the offshore wind energy plan. We argue that the spaces created by the pre-planning conjuncture offered the most conducive conditions for residents to voice concerns about the proposed project in a dialogical fashion, whereas the marine spatial planning and post-planning phases became mired in a therapeutic-style consultation, set alongside rigid and unreflexive interpretations and applications of legality. We conclude by setting out the limits of the Estonian marine spatial planning as a process for resolving conflicts, while offering an alternative model of handling such public controversies, which we call pragmatic adversarialism.